If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 = -2 + 3v Solving -20 = -2 + 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. -20 + -3v = -2 + 3v + -3v Combine like terms: 3v + -3v = 0 -20 + -3v = -2 + 0 -20 + -3v = -2 Add '20' to each side of the equation. -20 + 20 + -3v = -2 + 20 Combine like terms: -20 + 20 = 0 0 + -3v = -2 + 20 -3v = -2 + 20 Combine like terms: -2 + 20 = 18 -3v = 18 Divide each side by '-3'. v = -6 Simplifying v = -6
| 6a^2+4a=-11 | | 25-6x=19-5x | | 6m^2+13=5 | | .05x/259y=5550 | | .05x*259y=5550 | | 4x+28=10 | | 18=4w+2 | | .40x+1.25y=150 | | sinx+-1cosx+-1tanx=-1 | | 3y+4x-Y-2x-5y= | | 3(-6+9)+10x=1 | | x-4-3x-7=1/4 | | 4+7n+5n= | | 5x-12=8(x+3) | | 2a+a+5a= | | 55=4v+15 | | 7/9-4/6 | | 5x+2y=-34 | | z^3/25z*5/2z^2 | | 7b=-56-13-27 | | 2(3x-1)+2(x+2)=(3x+3)+(x+6)+(3x+3) | | -2-7r+6r-9= | | x/5-16=19 | | e^5x+1=e^7 | | 5n+8-1n=6(1n-1) | | X*x*2=122 | | 3(2b-4)+6=2(3b-6) | | -(2x-5)-(2x-5)+4=6(x-1)-(2x+7)+3 | | 2x-1/x=4/3 | | 6(a+3)=9 | | 5x^2-37=43 | | 5x+7/3=2x+9 |